Coxiella burnetii Affects HIF1α Accumulation and HIF1α Target Gene Expression - Hayek, Inaya; Szperlinski, Manuela; Lührmann, Anja (Frontiers in Cellular and Infection Microbiology, 2022)
HIF1α is an important transcription factor regulating not only cellular responses to hypoxia, but also anti-infective defense responses. We recently showed that HIF1α hampers replication of the obligate intracellular pathogen Coxiella burnetii which causes the zoonotic disease Q fever. Prior to development of chronic Q fever, it is assumed that the bacteria enter a persistent state. As HIF1α and / or hypoxia might be involved in the induction of C. burnetii persistence, we analyzed the role of HIF1α and hypoxia in the interaction of macrophages with C. burnetii to understand how the bacteria manipulate HIF1α stability and activity. We demonstrate that a C. burnetii-infection initially induces HIF1 stabilization, which decreases then over the course of an infection. This reduction depends on bacterial viability and a functional type IV secretion system (T4SS). While neither the responsible T4SS effector protein(s) nor the molecular mechanism leading to this partial HIF1α destabilization have been identified, our results demonstrate that C. burnetii influences the expression of HIF1α target genes in multiple ways. Therefore, a C. burnetii infection promotes HIF1α-mediated upregulation of several metabolic target genes; affects apoptosis-regulators towards a more pro-apoptotic signature; and under hypoxic conditions, shifts the ratio of the inflammatory genes analyzed towards a pro-inflammatory profile. Taken together, C. burnetii modulates HIF1α in a still elusive manner and alters the expression of multiple HIF1α target genes.